Measurement of Customer Perception regarding GSM vs WLL Services in India: Examining Customer Perception of GSM and WLL Services in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Quality of service and the ability to attract and retain customers dictate the success or failure of next-generation communications service providers. In today’s competitive environment, customers are quick to abandon services that do not meet expectations. The ease with which customers can switch from their current service to another, demands that providers deliver the highest possible levels of service quality and performance. To be successful, communications service providers must deliver positive customer experiences with rich, value-added services supported by comprehensive service quality management. To these effect-Mobile services has experienced the negative attributes of not being customer focused and realizes that quality is an attribute that creates customer satisfaction profitably. The study undertaken there to be mainly based on the primary data i.e. structured questionnaire is designed. The study also contains secondary data i.e. data from authenticated websites and journals for the latest updates just to gain an insight for the views of various experts.